Knowledge and Cervical Cervical Cancer Screening Self-efficacy in Jema’a Local Government Area of Kaduna State, Nigeria. (2023)
Background: Cervical Cancer (CC) is the second most common cancer among women in Nigeria. The women present at the late stage of the disease with no history of screening. Poor knowledge of CC has been reported which could have implications on screening uptake. The study assessed knowledge and cervical cancer screening self-efficacy among women in Jema'a LGA of Kaduna State. Methodology: A descriptive cross-sectional design was utilized and 382 women were selected using systematic random sampling. Data were collected using structured questionnaire. Data were analyzed using descriptive and inferential statistics- Chi-square test at 0.05 level of significance. Results: 167(43.7%) of the respondents had good knowledge on CC. Majority, 315 (82.5%) had high self-efficacy scores. Uptake was low as 227(59.4%) of the respondents had never been screened. There was a significant association between educational level and knowledge of CC screening (X-58.01; p=0.000), religion and self-efficacy (X= 7.873; p=0.020), education level and self-efficacy on CC screening (X-6.980; p=0.008). Conclusion: The women's knowledge and uptake of cervical cancer screening was poor; however, the respondents' self- efficacy was high. There is need for educational interventions to increase knowledge of cervical cancer screening and to make screening services available and accessible to enhance uptake.